Presurgical practice of supracondylar domosteotomie of cubitus varus deformity on 3D printed humerus (Transactions on Additive Manufacturing Meets Medicine, 2019)
Complicated fractures of bones can be difficult to treat, and there is a high probability that further operative corrections need to be carried out. In the present work, we present a case study, where a model of the humerus of a six-year-old male patient was 3D-printed from a segmented CT-dataset for a preoperative optimization of the geometric parameters of a supracondylar domosteotomy. The experimental simulation of the treatment has proven very useful to the physician, and the patient has been treated successfully.